Ethnopharmacological Survey on Otoglyphis pubescens (Desf.) Pomel in the Northeast of the Algerian Sahara - Ben Moussa, Mohammed Tahar; Nadji, Said; Amroune, Abdelkader; Benaldjia, Hanane; Oudjehih, Messaouda; Chaira, Safa; Chaira, Hassina (Archives of Pharmacy, 2025)
The utilization of phytotherapy is essential in the Algerian Sahara, where endemic plants such as Otoglyphis pubescens are used to address certain health issues. However, discrepancies in knowledge and application of these botanical resources may lead to toxicity and reduced efficacy. A questionnaire was prepared and interviews conducted among herbalists and common population to collect data according to the objectives set. Ethnobotany indices were calculated and comparison was made between the different subgroups of the sampled population. The most commonly used vernacular names for Otoglyphis pubescens are: Gartoufa, Gritfa, and Wazwaza. This plant is endemic and grows wild. The most commonly used parts are the whole aerial parts dried in the shade. This plant is used as herbal tea. The most commonly used preparation methods are maceration and infusion. This plant is used mainly for its therapeutic properties to address issues related to the treatment of digestive, genitourinary, and respiratory problems, and fever. According to the analysed indices, the interviewed populations showed high knowledge of the uses of O. pubescens, with subpopulations such as married individuals, females, persons aged over 60 years, the less educated, and the unemployed noting superior use of the plant. Variations are noted in the answers of the interviewed subjects and differences stood comparing to data reported in the literature, but close responses patterns were noted between the herbalists and the common population.